Knowledge and support from health workers are related to triple elimination examinations in pregnant women (HEALTH CARE: JURNAL KESEHATAN, 2023)
Pregnant women are a population at risk of contracting HIV/AIDS, hepatitis B and syphilis. The prevalence of HIV/ AIDS infection in pregnant women is 0.3%, syphilis is 1.7% and hepatitis B is 2.5%. 90% of these infectious diseases are transmitted directly to the baby which can occur during pregnancy, childbirth and during breastfeeding. Maternal to infant elimination from HIV/AIDS, syphilis and hepatitis B can be done with triple elimination. The purpose of this study is to determine the relationship between knowledge, support of health workers and triple elimination examination in pregnant women. Correlation descriptive research design. Research was conducted in the working area of the Sedinginan Health Center country Rokan Hilir. The population in this study was all pregnant women in the working area of the Sedinginan Health Center. The study sample totaled 242 people. Data analysis using the chi square test. The results of the study have a knowledge relationship with triple elimination examination (p = 0,000), there is a relationship between health worker support and triple elimination examination (p = 0,000). It is expected for health workers to be able to carry out health promotion about triple elimination examinations, especially in pregnant women.